Using intervention mapping to design, implement and evaluate an executive function training intervention - Allom, Vanessa; Mullan, B. (Springer, 2016)
Introduction: Healthy eating behaviors, such as minimizing dietary fat intake, reduce the risk of numerous negative health consequences including obesity. Currently, very few interventions designed to reduce unhealthy eating are effective. Higher order cognitive process referred to as executive functions, have been proposed to influence the adoption and maintenance of healthy eating behaviors. A multi-method approach based on the Intervention Mapping Protocol was used to design, implement and evaluate an executive function training intervention to reduce unhealthy eating behavior. Methods: Qualitative interviews were conducted to assess the needs of the target population and establish the factors involved in the maintenance of healthy eating behavior. Subsequently, a cross-sectional study was conducted to test whether the factors deemed important were associated with eating behavior. A meta-analysis of current executive function and eating behavior interventions was conducted to identify effective components of existing interventions. An intervention was then designed based on these results and implemented in an undergraduate sample (N = 82) and evaluated. Finally, the intervention was replicated in a community sample (N = 78) and the acceptability and feasibility of the intervention was assessed. Results: The intervention led to a reduction in body mass index, which was mediated by changes in vulnerability to ego-depletion. These results were only partially replicated, and did not persist over time. Participants found the intervention to be highly acceptable. Conclusions: These findings provide an example of an intervention designed and evaluated using intervention mapping and highlight the importance of careful theory-based intervention planning for health promotion.